THE IMPACT OF AIR TRAFFIC INCREASES ON THE SAFETY OF AIR OPERATIONS IN THE POLISH AIRSPACE - Jarosław KOZUBA; Jacek KRAWCZYK; Łukasz KORYTEK (Scientific Journal of Silesian University of Technology. Series Transport)
Polish airspace is available to all its users on an equal basis . The state is obliged to ensure the safety of aviation operations within its air borders and to safeguard the fluidity of air traffic through the appropriate operationalization of telecommunications, navigation, signal codes and proper airport infrastructure, as well as area navigation . Increasing air traffic requires constant amelioration of airspace structures and the management of airspace and air traffic flow, in accordance with international laws and country-specific circumstances. This article discusses the changes in air traffic throughput from 1997 to 2016 and analyses air traffic and its influence on airspace safety, based on statistics from the Polish Air Navigation Services Agency (PANSA). The article also examines the increase in the number of aircraft, taking into account the delays generated in European and Polish airspace, while outlining the changes in air traffic management (ATM), as implemented by the PANSA.